2024
DOI: 10.1002/anie.202316364
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Prospects in Understanding London Dispersion Interactions in Molecular Chemistry

Lars Rummel,
Peter R. Schreiner

Abstract: London dispersion (LD) interactions are the main contribution of the attractive part of the van der Waals potential. Even though LD effects are the driving force for molecular aggregation and recognition, the role of these omnipresent interactions in structure and reactivity had been largely underappreciated over decades. However, in the recent years considerable efforts have been made to thoroughly study LD interactions and their potential as a chemical design element for structures and catalysis. This was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 273 publications
0
5
0
Order By: Relevance
“…7–10 The result is in line with conventional views indicating that van der Waals interactions are primarily governed by the London dispersion force. 43–45…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7–10 The result is in line with conventional views indicating that van der Waals interactions are primarily governed by the London dispersion force. 43–45…”
Section: Resultsmentioning
confidence: 99%
“…50 Meanwhile, the essential definition of the C–H⋯π “interaction” should remain inconclusive under the refinement of the London dispersion force, which is the predominant factor in the C–H⋯π interaction. 44,45 At this moment, a minimum prerequisite for the C–H⋯π “interactions” may be the interatomic distance ranging from 2.83 Å to 3.08 Å (−6.2% < p CH < 7.5%) at the level of pure van der Waals interactions. This range fulfills the empirical limit of d < 3.3 Å (−17.4 < p CH ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several computational studies also emphasized the significance of dispersion in the stacking behavior. Sherill et al reported a surprising finding using high-level computational analyses that all substituted benzene dimers have more favorable binding interactions than a benzene dimer in the sandwich configuration, which points to a strong influence of dispersion forces and direct interactions between benzene and substituents. Wheeler and Houk also provided compelling evidence that the substituent effects in the benzene dimer are due to direct interactions of the substituents with the unsubstituted benzene . Those arguments were also supported by the related work of several groups such as Grimme, Hobza, Shimizu, Sherill, and Schreiner . In addition, the weak intermolecular π–π interactions might be swamped out by the desolvation effect in polar solvents. , Consequently, there is a pressing demand for new methods that can be used to elucidate the origin of π–π interactions.…”
Section: Introductionmentioning
confidence: 93%
“…The root cause of the “methyl/ethyl problem”or generally two alkyl moietieslies in the very subtle differences in their stereoelectronic properties. In terms of catalyst design, this leaves very few options other than steric size differences (as judged by van der Waals surfaces) utilized, e.g., in “confined” catalysts or London dispersion (LD) interactions. It has been demonstrated in the past few years that LD interactions indeed can be a decisive element in catalyst design , by employing dispersion energy donors (DEDs), , but would these be sufficient to meet the methyl/ethyl challenge? If so, which DEDs are the most suitable, and how can they be identified without having to generate a large catalyst library?…”
Section: Introductionmentioning
confidence: 99%